Facilitation of AMPA Receptor Synaptic Delivery as a Molecular Mechanism for Cognitive Enhancement - Knafo, Shira; Venero, César; Sánchez-Puelles, Cristina; Pereda-Peréz, Inmaculada; Franco, Ana; Sandi, Carmen; Suárez, Luz M.; Solís, José M.; Alonso-Nanclares, Lidia; Martín, Eduardo D.; Merino-Serrais, Paula; Borcel, Erika; et al. (PLOS Biology, 2012)
A small peptide from a neuronal cell adhesion molecule enhances synaptic plasticity in the hippocampus and results in improved cognitive performance in rats.